2021
DOI: 10.1002/hep.31604
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 4α Prevents the Steatosis‐to‐NASH Progression by Regulating p53 and Bile Acid Signaling (in mice)

Abstract: Background and Aims Hepatocyte nuclear factor 4α (HNF4α) is highly enriched in the liver, but its role in the progression of nonalcoholic liver steatosis (NAFL) to NASH has not been elucidated. In this study, we investigated the effect of gain or loss of HNF4α function on the development and progression of NAFLD in mice. Approach and Results Overexpression of human HNF4α protected against high‐fat/cholesterol/fructose (HFCF) diet–induced steatohepatitis, whereas loss of Hnf4α had opposite effects. HNF4α preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…In mouse models of high-fat diet (HFD) and high-fat high-cholesterol (HFCF) diet, increasing HNF4α expression protected against NASH by reducing expression of genes involved in inflammation, fibrogenesis and senescence (e.g., TNFα, IL6, IL1b, MCP1, F4/80 and p53), liver injury and ROS production. Deletion of p53 in hepatocytes with HNF4α overexpression (AAV8-ALB-hHNF4α) diminished the protective effect, suggesting that HNF4α exerted its effect through p53 [ 76 ]. Another study explored the potential global role of p53 in the complex network of pathways and cell–cell interactions involved in mediating injury and local inflammation in chronic liver disease and NAFLD [ 77 ].…”
Section: The Role Of Cellular Senescence In Fatty Liver Diseasementioning
confidence: 99%
“…In mouse models of high-fat diet (HFD) and high-fat high-cholesterol (HFCF) diet, increasing HNF4α expression protected against NASH by reducing expression of genes involved in inflammation, fibrogenesis and senescence (e.g., TNFα, IL6, IL1b, MCP1, F4/80 and p53), liver injury and ROS production. Deletion of p53 in hepatocytes with HNF4α overexpression (AAV8-ALB-hHNF4α) diminished the protective effect, suggesting that HNF4α exerted its effect through p53 [ 76 ]. Another study explored the potential global role of p53 in the complex network of pathways and cell–cell interactions involved in mediating injury and local inflammation in chronic liver disease and NAFLD [ 77 ].…”
Section: The Role Of Cellular Senescence In Fatty Liver Diseasementioning
confidence: 99%
“…This is consistent with previous observations of SOCS3 as a direct target of STAT3 and the co-activation of STAT3 and SOCS3 in a human liver organoid model of fibrosis(72). We noticed that several genes in Figure 5F are direct targets of p53, which plays an essential role in driving apoptosis in NASH(47, 73, 74). Our analysis revealed that CDKN1A (p21) is uniquely associated with the STAT3 cistrome ( Figure 5F, G ), whereas other p53 targets (e.g., THBS1 , AEN , and GADD45B ) are associated with multiple TF cistromes ( Figure 5F, H ).…”
Section: Resultsmentioning
confidence: 95%
“…Differential transcription analysis identified 879 and 651 genes that are more transcriptionally active in NP and NR, respectively ( Figure 1E ; p < 0.05, padj < 0.2, normalized counts > 100, log2FC < or > 0 by DESeq2). The genes that are more transcriptionally active in NP than NR (hereafter, referred to as NP-activated genes) are enriched in pathways involved in neutrophil activation, immunity, and cytokine responses ( Figure 1F ), such as IL1B (37), IL6 (38), CCL2 (encoding MCP-1)(39, 40), CCL20 ( 16 ), HIF1A (41), TREM1 (42), PKM (43), CXCR2 (44), CRP (45, 46) , IL32 (47), and CD44 (48) ( Figure 1H ). The genes that are more transcriptionally active in NR than NP (hereafter, referred to as NR-activated genes) are enriched in pathways involved in fatty acid metabolism ( CPT2, ACADL, AIG1, ACAA2, ACSM5, ACOX2, BDH2, HAO2 ) and xenobiotic processes ( CYP2J2 )( 49 )( Figure 1G-H ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it would be interesting to assess the metabolic effects of PFOA in PXR-knockout mice and in human hepatocytes with PXR silencing. (3) Reduction in HNF4α protein levels and activity [152,166], an effect which is expected to impair FAO and VLDL secretion [167].…”
Section: Perfluorooctanoic Acidmentioning
confidence: 99%